Cardiopulmonary Complications During and After Endoscopy in Elderly Patients:a Prospective Study - Yusuf, Sabrina Munggarani; Dwimartutie, Noto; Maulahela, Hasan; Harimurti, Kuntjoro; Rinaldi, Ikhwan; Yunihastuti, Evy; Fauzy, Achmad; Putranto, Rudi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: The high incidence of gastrointestinal and pancreaticobiliary diseases among elderly has led to increased endoscopic procedures in this population. Previous studies indicate a higher risk of cardiopulmonary complications during and after endoscopy in elderly patients compared to younger individuals. This study investigated the incidence and contributing factors of endoscopy-related cardiopulmonary complications in elderly patients.Methods: A prospective cohort study was conducted on 194 patients aged ≥ 60 years undergoing endoscopy at the Gastrointestinal Endoscopy Center, Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia, from August to October 2023. Consecutive sampling method was used. Multivariate analysis with logistic regression was conducted. Results: Among the 194 patients included, 49.52% experienced cardiopulmonary complications. The most common complications were tachycardia (23.20%), hypoxemia (15.03%), and hypotension (6.20%). Multivariate analysis identified the complexity of the procedure (ASGE level ≥ 3) as a significant risk factor (RR 1.505, 95% CI 1.039-2.179; p=0.03), while mild-moderate sedation was associated with a reduced risk of complications (RR 0.668, 95% CI 0.458-0.975; p=0,037). Conclusion: The incidence of cardiopulmonary complications during and after endoscopy is high among Indonesian elderly. Procedure complexity is an independent risk factor, whereas mild-moderate sedation mitigates the risk. In opposite, advanced age, multimorbidities, high ASA class, long duration of procedure, poor nutritional and functional status, and type of procedure did not affect outcomes